Investigation and Analysis of the role of rhyme in the use of Arabic words in Persian poetry - Tahereh Ghasemi (مطالعات زبانی و بلاغی)
The influence of Islam and the development and spread of the Arabic language in neighboring countries such as Iran, led to the use of the Arabic words in the Persian language. Persian was so mixed with Arabic that it is now impossible to separate Arabic words from Persian language. Concerning the significant role of rhyme in poetry, especially in odes, poets chose words from Arabic when they faced hassles in matching the rhyme. When we examine the course of odes in Persian language, many Arabic words can be seen in the rhyme scheme, even in the earliest remaining odes. In addition, poets have used obscure and abandoned Arabic words in the rhyme of their poems. In the early prose texts, however, very few Arabic words were used. Some poets such as Manūchehrī, Anvarī and Khāqānī have used more Arabic words in their poems. Meanwhile, in sonnet, obscure and abandoned Arabic words have been used less frequently in Persian language. In Masnavis, rhymes follow the style of their era; that is, Arabic words are few in the first centuries of Persian poetry and are used more often in the following centuries. Also, the last letter of the rhyme affects the word selection of the rhyme significantly. If the poet chooses the letter " گ", the rhyming words become Persian. This article examines the role of rhyme in the use of Arabic words, starting from early poets such as Rūdakī, Farrokhī, and Manūchehrī. The statistical results of the use of Arabic rhymes are then shown in the form of a diagram.